OncoRTT: Predicting novel oncology-related therapeutic targets using BERT embeddings and omics features - Thafar, Maha A.; Albaradei, Somayah; Uludag, Mahmut; Alshahrani, Mona; Gojobori, Takashi; Essack, Magbubah; Gao, Xin (Frontiers in Genetics, 2023)
Late-stage drug development failures are usually a consequence of ineffective targets. Thus, proper target identification is needed, which may be possible using computational approaches. The reason being, effective targets have disease-relevant biological functions, and omics data unveil the proteins involved in these functions. Also, properties that favor the existence of binding between drug and target are deducible from the protein's amino acids sequence. In this work, we developed OncoRTT, a deep learning (DL)-based method for predicting novel therapeutic targets. OncoRTT is designed to reduce suboptimal target selection by identifying novel targets based on features of known effective targets using DL approaches. First, we created the "OncologyTT" datasets, which include genes/proteins associated with ten of the more prevalent cancer types. Then, we generated three sets of features for all genes: omics features, the proteins’ amino-acid sequence BERT embeddings, and the integrated features to train and test the DL classifiers separately. The models achieved higher prediction performance in terms of area under the curve (AUC) and achieved AUCs greater than 0.88 for all cancer types, with a maximum of 0.95 for leukemia. Also, OncoRTT outperformed the state-of-the-art method using their data in five out of seven cancer types commonly assessed by both methods. Furthermore, OncoRTT predicts novel therapeutic targets using new test data related to the seven cancer types. We further corroborated these results with different validation evidence using the Open Targets Platform and a case study focused on the top-10 predicted therapeutic targets for lung cancer.